Análise da adoção de tecnologias da Indústria 4.0 por pequenas e médias empresas do setor de usinagem - Baio Junior, Antonio Arnaldo (Universidade Federal de São Carlos, 2022)
New information and communication technologies (ICTs), such as internet of things, wireless network sensors, mobile internet, big data, cloud computing, embedded systems, additive manufacturing and autonomous robots have been adopted by companies from different industries. This movement is treated in the literature as a fourth technological revolution, also known as “Industry 4.0”. Despite the economic, social and environmental potential benefits of Industry 4.0 technologies, the level of adoption by small and medium-sized Brazilian companies still appears to be low. This work aimed to analyze the level of adoption and compare characteristics of adopters and non-adopters of Industry 4.0 technologies. Primary data for the year 2021 were collected through a structured questionnaire applied to a sample of 30 small and medium-sized companies in the metallurgical sector, which operate with machining processes, in the state of São Paulo. Data were analyzed using descriptive statistics measures, statistical tests to compare means/frequency and an econometric regression model. The 4.0 technologies adopted by the sample companies were: Cloud Computing (10 companies), Horizontal and Vertical Integration Systems (5 companies), Big Data (4 companies) and Industrial Internet of Things (4 companies). The comparative analysis between the characteristics of adopters and non-adopters showed that: (1) adopters have, much more frequently, employees with ICT skills and also more frequently hire ICT consulting services; (2) the use of ERP and MRP systems is much higher among companies adopting Industry 4.0 technologies; (3) adopters participate more frequently in cooperation programs with Universities, Science and Technology Institutes or Technological Research and Development Promotion Agencies; (4) companies that adopt 4.0 technologies have a greater perception of relative advantage and compatibility of these technologies. The results of the estimated econometric model corroborate the importance of the availability of skilled labor in ICTs, the prior adoption of other management technologies and the perception of compatibility of 4.0 technologies to determine the intensity in use of these technologies by the companies in the sample. The study results are consistent with the empirical literature review and with the theoretical TOE model.
Analysis of the adoption of Industry 4.0 technologies by small and medium-sized companies in the machining sector
Keywords: Indústria 4.0; Tecnologias de Informação e Comunicação; Pequenas Empresas; Adoção de Tecnologias; Industry 4.0; Information and Communication Technologies; Small Business; Technology Adoption; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO